Cognitive psychology : a student's handbook - Eysenck, Michael W.; Keane, Mark T., 1961- (Routledge, 1990)
"The fully updated eighth edition of Cognitive Psychology: A Student's Handbook provides comprehensive yet accessible coverage of all the key areas in the field ranging from visual perception and attention, through to memory and language. Each chapter is complete with key definitions, practical real-life applications, chapter summaries and suggested further reading to help students develop an understanding of this fascinating but complex field"--